Prediction of Extrathyroidal Extension Using Ultrasonography and Computed Tomography - Doh Young Lee; Tack-Kyun Kwon; Myung-Whun Sung; Kwang Hyun Kim; J. Hun Hah (International Journal of Endocrinology)
Objectives. The aim of the present study was to evaluate the value of high-resolution ultrasound (US) and computed tomography (CT) scan for preoperative prediction of the extrathyroidal extension (ETE). Methods. We analyzed the medical records of 377 patients with papillary thyroid carcinoma (PTC) with preoperative US and CT scan to calculate the sensitivity, specificity, and positive and negative predictive values of characteristics imaging features (such as contact and disruption of thyroid capsule) for the presence of ETE in postoperative pathologic examination. We also evaluated the diagnostic power for several combinations of US and CT findings. Results. ETE was present in 174 (46.2%) based on pathologic reports. The frequency of ETE was greater in the patients with greater degrees of tumor contact and disruption of capsule, as revealed by both US and CT scans (positive predictive value of 72.2% and 81.8%, resp.). Considering positive predictive values and AUC of US and CT categories, separately or combined, a combination of US and CT findings was most accurate for predicting ETE (83.0%, 0.744). Conclusions. This study suggests that ETE can be predicted most accurately by a combination of categories based on the findings of US and CT scans.